Finite Betweenness Relational Structures Are Not Fraïssé - Balchev, Stanislav; Szeptycki, Paul (Sarajevo Journal of Mathematics, 2024)
We consider the class of ﬁnite sets with ternary relations satisfying certain axioms of betweenness. We show this class and a related larger class are not Fraïssé, correcting a claim in [2]. We also consider restricted Ramsey properties of these classes.